THE EFFECT OF CONCENTRATE PROVISION ON NUTRIENT DIGESTIBILITY OF POST-PARTUM BALI COWS - N. L. P., Kristina; Mariani, N. P.; Putri, T. I. (Jurnal Peternakan Tropika; Vol 8 No 2 (2020): Vol. 8 No. 2 Tahun 2020; Mei - Agustus, 2020)
This study aims to determine the level of addition of concentrate that is able to improve the digestibility of nutrient ration in post-partum bali cow. This research was conducted at the Sedana Bakti Pertiwi Livestock Group in Kesiman Village, East Denpasar for three months, used 12 post-partum bali cows. Analysis of ration and feces samples was carried out at the Animal Nutrition and Feed Laboratory of the Faculty of Animal Husbandry, Udayana University for one month. The experimental design used was a randomized block design (RBD) with three treatments and four replications. The treatments were ad lib forage (elephant grass, field grass, corn stalks and corn husk) (P0), 0.5kg concentrate + given ad lib forage (P1), 1kg concentrate + given ad lib forage (P2). Variables observed included dry matter digestibility, organic matter digestibility, crude protein digestibility, and crude fiber digestibility. The results showed that the higher the addition of concentrate in the ration, the higher the digestibility of dry matter and the highest digestibility of organic cow, with values of 63.73% -71.18% and 88.45% -74.70% respectively statistically showed a significant difference (P <0.05). While the digestibility of crude protein and crude fiber digestibility increased with values of 66.88% -73.32% and 74.70% -77.45% respectively but statistically the results showed no significant difference (P> 0.05). Based on the results of the study it can be concluded that the provision of rations with concentrations of 0.5kg and 1kg have not been able to increase the digestibility of nutrient ration maximally. Keywords: concentrate, nutrient digestibility, post-partum bali cow